The Acta Pekinensia or Historical records of the Maillard de Tournon legation / Volume 2 September 1706-December 1707 / by Kilian Stumpf, SJ ; edited by Paul Rule, Claudia von Collani - Stumpf, Kilian (The Acta Pekinensia or Historical records of the Maillard de Tournon legation, 2019)
The 'Acta Pekinensia' is a Latin manuscript found in the Jesuit Roman Archives. It is a record of the papal legation to China of Charles Maillard de Tournon, from his arrival in China to his death in Macau. It was compiled by Kilian Stumpf, a German Jesuit missionary/scientist serving at the court of the Kangxi Emperor of China. Stumpf was in a privileged position to record day by day the events of this crucial episode not only in the history of Christianity in China but in Chinese-Western relations. This annotated translation provides a full documentation and an acute and lively commentary on the clash of values which resulted in the failure of the legation and the condemnation of Chinese Rites